Respuesta :

Answer:

Step-by-step explanation:

Given :

KM bisects JKL

To Prove :

m∠MKL = [tex]\frac{1}{2}\angle \text{JKL}[/tex]

                    Statements                                      Reasons

1). KM bisects ∠JKL                                 1). Given

2). m∠JKM = m∠MKL                              2). Definition of congruent angles

3). m∠JKM + m∠MKL = m∠JKL              3). Angle addition postulate

4). m∠MKL + m∠MKL = m∠JKL              4). Substitution property of equality

5). 2m∠MKL = m∠JKL                            5). Distributive property

6). m∠MKL = [tex]\frac{1}{2}\angle \text{JKL}[/tex]                               6). Division property of equality